Tracing pre-diploma students' academic performance : a case of Universiti Teknologi MARA Malaysia/ Mazlina Mahdzar ... [et al.] - Mahdzar, Mazlina; Jaapar, Aini (Dr.); Wan Mohd Zain, Wan Zuraida; Ismail, Ismassabah; Abd Razak, Rosdiana (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
This research investigates the academic performance and progress of the pre-diploma students of Universiti Teknologi MARA (UiTM) after continuing their studies at the Faculty of Hotel and Tourism Management (FHTM) UiTM. The performance of all pre-diploma students who had enrolled in UiTM for the year 2010 to 2017 was analyzed descriptively using Microsoft Excel. The enrolment data for this program and the faculty were obtained from UiTM's Centre for Strategic Planning and Information. This study reports that a total of 3612 pre-diploma students were successful in their pre-diploma program and managed to further their studies at the diploma level with the Faculty of Hotel and Tourism Management. Additionally, 369 students continued their study at bachelor's degree and another five at master's level. Based on this study, their progress in academic performance showed that UiTM's Pra Pendidikan Tinggi program has succeeded in helping the students further their studies at a higher level.